Dao Philosophy and its Religious Tradition - Dhammajothi, M. (Ethika Publishers, 2012)
This book written in Sinhala is about Laozi, a great Chinese Philosopher and his Philosophy which is somewhat similar to Confucius philosophy, the main doctrine and teaching at the time, who sustained Chinese religions and philosophies with great effort. This book provides information in greater detail on the founder of the tradition, Laos and also other followers, the main teachings of Dao and De. Furthermore, the post developmental changes, trends and its direct influence on Chinese culture are also widely discussed in this book. The back cover is written by Ven. Prof. Devalagama Medhananda Thero at the Faculty of Pali and Buddhist Studies, University of Kelaniya.